1995
DOI: 10.2307/3870191
|View full text |Cite
|
Sign up to set email alerts
|

Seed Coat: Associated Invertases of Fava Bean Control Both Unloading and Storage Functions: Cloning of cDNAs and Cell Type: Specific Expression

Abstract: We have studied the molecular physiology of photosynthate unloading and partitioning during seed development of fava bean (Vicia faba). During the prestorage phase, high levels of hexoses in the cotyledons and the apoplastic endospermal space are correlated with activity of cell wall-bound invertase in the seed coat. Three cDNAs were cloned. Sequence comparison revealed genes putatively encoding one soluble and two cell wall-bound isoforms of invertase. Expression was studied in different organs and tissues of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
113
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 0 publications
7
113
0
1
Order By: Relevance
“…The present study was extended to seed maturity (80 DAA) and was based on plants grown in the field rather than in growth chambers. However, in agreement with Weber et al (1995), we have demonstrated that acid invertase activity is extremely low in the reserve cotyledon tissue throughout development. Heim et al (1993) proposed that storage product synthesis is dependent on the Suc synthase pathway and a low hexose to SUC ratio.…”
Section: Dlscusslonsupporting
confidence: 69%
See 2 more Smart Citations
“…The present study was extended to seed maturity (80 DAA) and was based on plants grown in the field rather than in growth chambers. However, in agreement with Weber et al (1995), we have demonstrated that acid invertase activity is extremely low in the reserve cotyledon tissue throughout development. Heim et al (1993) proposed that storage product synthesis is dependent on the Suc synthase pathway and a low hexose to SUC ratio.…”
Section: Dlscusslonsupporting
confidence: 69%
“…However, no comparative data have been presented on invertase and SUC synthase enzyme activities in the seed coats. The work of Weber et al (1995) concentrates primarily on the prestorage phase of seed development, and, although Heim et al (1993) present results for the storage phase of seed development, they do so only as far as 50 d after flowering.…”
Section: Dlscusslonmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CWINs are central to phloem unloading and carbon partitioning, especially in cellular sites lacking symplasmic (plasmodesmal) connections (Patrick and Offler, 2001;Weschke et al, 2003). A positive correlation between CWIN activity and seed development has been observed in maize (Zea mays; Cheng et al, 1996;Vilhar et al, 2002;Chourey et al, 2006), faba bean (Vicia faba; Weber et al, 1995Weber et al, , 1996, barley (Hordeum vulgare; Weschke et al, 2003;Sreenivasulu et al, 2004), rice (Oryza sativa; Hirose et al, 2002;Wang et al, 2008), and tomato (Solanum lycopersicum; Zanor et al, 2009). With an exception in tobacco (Nicotiana tabacum; Tomlinson et al, 2004), high and low Glc-to-Suc ratios generally favor cell division or promote cell differentiation, respectively, during seed development (for review, see Weber et al, 2005).…”
mentioning
confidence: 94%
“…The authors reported that Suc synthase had consistently higher activity than invertase throughout endosperm development, and that invertase activity did not change appreciably. Weber et al (1995) studied the molecular physiology of photosynthate unloading and partitioning during seed development of fava bean and reached the opposite conclusion. During the prestorage phase, they found that high levels of hexoses in the cotyledons and the apoplastic endospermal space were correlated with high levels of cell wall-bound invertase in the seed coat.…”
Section: Invertases and Suc Allocationmentioning
confidence: 99%